ANALISIS KESULITAN PADA MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL PADA PEMBELAJARAN DARING - Winda Nuraeniah; Nelly Fitriani; Risma Amelia (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
This study aims to determine the student difficulties in the SPLDV material. This research is a quantitative descriptive study that examines students difficulties yn the SPLDV material based on indicators (1) Modeling the SPLDV (2) Analyzing the completion of the SPLDV (3) Finding the solution to the SPLDV using Elimination and Subtitution methods (4) Summarizing the grap and (5) Linking the SPLDV in everyday life. The research was carried out in one of the private junior high school in Padalarang. The subjects of this research ere 15 students who have studied the SPLDV material. The data collection is by giving questions to student. The data analysis technique went though three stages, namely data reduction, data presentation, and conclusion. The results of the study show that there are still students who have difficulty in concluding the indicators of the graph, this can be seen from the average value of 27% which belong to the very poor category. It is also found that the factors that make the indicators on the SPLDV material esperience difficulties are the lack of accuracy when working on problems, difficulty in classifying known objects, and not mastering the concepts and principles of SPLDV.